2018
DOI: 10.1002/cphc.201701197
|View full text |Cite
|
Sign up to set email alerts
|

Further Studies on How the Nature of Zeolite Cavities That Are Bounded by Small Pores Influences the Conversion of Methanol to Light Olefins

Abstract: A series of small-pore zeolites are synthesized and investigated as catalysts for the methanol-to-olefins (MTO) reaction. Small-pore zeolites SSZ-13, SSZ-16, SSZ-27, SSZ-28, SSZ-52, SSZ-98, SSZ-99, SSZ-104, SSZ-105 and an ITQ-3-type material are synthesized, and the results from their use as catalytic materials in the MTO reaction compared to those obtained from SAPO-34. The production of propane that tends to correlate with catalytic material lifetime (higher initial propane yields lead to shorter lifetimes) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
73
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(80 citation statements)
references
References 26 publications
5
73
0
2
Order By: Relevance
“…77 Similarly, the more spacious cage of ERI delivers higher selectivity to ethylene in comparison to CHA, which might be due to narrower window openings of ERI (3.6 x 5.1 Å) in comparison to CHA (3.8 x 3.8 Å). 80 Medium pore 10-ring zeolites, on the other hand, are composed of straight and/or curved channels (Fig. 5c-f).…”
Section: Influence Of Zeolite Topology On Product Selectivitymentioning
confidence: 99%
“…77 Similarly, the more spacious cage of ERI delivers higher selectivity to ethylene in comparison to CHA, which might be due to narrower window openings of ERI (3.6 x 5.1 Å) in comparison to CHA (3.8 x 3.8 Å). 80 Medium pore 10-ring zeolites, on the other hand, are composed of straight and/or curved channels (Fig. 5c-f).…”
Section: Influence Of Zeolite Topology On Product Selectivitymentioning
confidence: 99%
“…It has also been reported that the contribution of each of the two pathways to the global conversion of methanol, and therefore to the final light olefin product distribution, depends on the topology of the zeolite cage. 3,19,[21][22][23] Very recently, the concept of cage-defining ring size has been introduced to classify small-pore cage-based zeolites into four structural categories that differ in their light olefin product distribution. 24 However, the chemical origin of this behavior has not been clearly explained yet.…”
Section: Introductionmentioning
confidence: 99%
“…It has been described in the literature that when small pore zeolites containing cavities in their structure are used in the MTO reaction, the product selectivity towards different light olefins as well as the catalyst lifetime are influenced by the framework structure. 15,26,27 That observation could be explained by the ability of the cavities present in the zeolite to favor the formation of different polyalkylated aromatics depending on their size/shape. In general, small pore zeolites with very large cavities [i.e.…”
mentioning
confidence: 99%
“…26 On the other hand, different small pore zeolite structures containing cavities with intermediate sizes, though prepared with similar crystal sizes and chemical compositions, present different selectivities towards ethylene and propylene. [28][29][30][31][32] For instance, the high-silica SSZ-39 (AEI, cage dimensions: 12.6x11.2 Å, C3 = /C2 = 2.4) and RUB-13 (RTH, cage dimensions: 11.6x10.0 Å, C3 = /C2 = 3.4) zeolites tend to give higher propylene/ethylene ratio compared to high-silica CHA (cage dimensions: 11.7x10.2 Å, C3 = /C2 = 1.0) zeolite (see Supplementary Figure 1), 27,28,30 though the size of the pores and cavities, especially in the case of RTH and CHA, are very close. According to these results, it could be envisioned that even small differences in the zeolite cages may stabilize in a different manner the formation of the HP aromatic intermediates shown in Figure 1, favoring the side chain or the paring mechanism, and changing in that way the selectivity within the olefins obtained.…”
mentioning
confidence: 99%